The Roles, Tasks and Social Rank of a Man and a Woman in a Family on the Basis of Selected Women’s Journals from the Years 1864–1914 - Kalinowska-Witek, Barbara (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
The man played the dominant role in the Polish family for centuries. He satisfied the needs of its members. He made all the important decisions solo. He also represented the family to the outside world. The role of women was usually narrowed to act as childminder, hostess and educator of the young generation. This last task was especially important during a period of national captivity, however, it did not result in any visible improvement of the station of women in the family. In the second half of the 19th century women’s magazine publishers had begun to demand of fathers a greater interest of their own offspring than had previously been the case, and especially their education and upbringing. At the same time they pointed out that the wife should support her husband in his difficult moments.
Keywords: patriarchal family; father; mother; men; women; women's magazine; family